EKSPANSI CANTOR DAN PERLUASANNYA - Nova, Sanjung; Sulaiman, Raden (Sains & Matematika, 2014)
This article discuss Cantor set, Cantor expansion and extended of Cantor expansion. These expansions are another ways toexpress a number except decimal system and binary system. How to express a natural number with Cantor expansion and extendedof Cantor expansion are discribed too. Some examples are given and we proved that Cantor expansion is special case of extended ofCantor expansion.